The intra-class heterogeneity of immunophenotyping and immune landscape in oesophageal cancer and clinical implications - Yujie Xie; Xiaoshun Shi; Ying Chen; Bomeng Wu; Xiaolin Gong; Weicheng Lu; Wanli Lin (Annals of Medicine, 2021)
AbstractBackground The response rate and survival benefit of immunotherapy vary among patients, implying specific immune status of an individual could be associated with the effect of immunotherapy. However, in-depth studies of immune subtypes (ISs), immune landscape and tumour microenvironment of oesophageal cancer (ESCA) and their clinical implications are less reported.Methods We first accessed data from publicly available databases and preprocessed it based on a standard protocol. Then, ISs were identified by unsupervised learning. Thereafter, the association of these ISs and tumour mutation burden (TMB), biomarkers of chemotherapy-induced immune response, tumour markers were also assessed. In addition, the immune characteristics, immune landscape, co-expression network of immune genes, and clinical implications were visualized and analysed.Results We identified three immunoclusters based on immune-associated genes with intra-class heterogeneity and prognostic value. Cluster-specific associations with TMB, markers of chemotherapy-induced immune response, and tumour markers were revealed. A 4-gene signature (risk score= −0.16514291×BHLHE22−0.03964046×MXRA8−0.15242778×SLIT2−0.05553572×SPON1) based on co-expressed genes in the immunoclusters was developed and externally validated.Conclusions In summary, we identified clinically relevant immunoclusters in both adenocarcinoma and squamous cell carcinoma of oesophagus, revealing the necessity of assessing the complexity and diversity of immune microenvironment for cancer immunotherapy.